The equity trader course - Schwartz, Robert A. (Robert Alan), 1937-; Francioni, Reto.; Weber, Bruce W., 1961- (Hoboken, N.J. : John Wiley, 2006)
"In The Equity Trader Course, Robert Schwartz, Reto Francioni, and Bruce Weber - along with a number of industry leaders who have contributed special pieces for the chapters of this book - provide a comprehensive course in equity trading for both the seasoned professional and serious independent trader. This detailed guide delivers key information on the dynamics of equity trading and shows you how to make the most of your time in the markets."--BOOK JACKET.
Ch. 1. Getting a grip on trading -- Ch. 2. All about liquidity -- Ch. 3. How to use limit and market orders -- Ch. 4. Choosing between continuous trading and a periodic call auction -- Ch. 5. Market intermediaries : nuts 'n' bolts and challenges -- Ch. 6. The road to technical analysis and algorithmic trading -- Ch. 7. Performance measurement -- App. Prices and returns.
Includes bibliographical references (p. 383-393) and index.
Keywords: Stocks